Expression of urokinase-type plasminogen activator and its receptor in squamous cell carcinoma of the oral tongue - SERPA,Marianna Sampaio (2018)
Abstract Urokinase-type plasminogen activator (uPA) and its receptor (uPAR) act in the proteolysis of basement membrane and extracellular matrix structures, facilitating tumor invasion. The purpose of this study was to evaluate the relationship between these proteins and clinicopathological parameters in squamous cell carcinoma of the oral tongue (SCCOT). Sixty cases of SCCOT were submitted to immunohistochemistry and analyzed semiquantitatively at the invasion front and in the tumor core. The results were associated with lymph node metastasis, clinical stage, locoregional recurrence, clinical outcome and histological grade of malignancy. A higher expression of uPA was observed in cases of tumors of high-grade versus low-grade malignancy (p = 0.010). Moreover, the cases with the worst pattern of invasion presented an overexpression of uPA (p = 0.011). The presence of locoregional recurrence was associated with uPAR (p = 0.039), and the expression of both biomarkers was much higher at the invasion front than in the tumor core (p < 0.001). The results suggest uPA and uPAR are involved in the progression and aggressiveness of SCCOT, mainly at the tumor-host interface.